Night of fire a novel - Thubron, Colin 1939- (Harper, 2017)
"Award-winning, bestselling novelist and travel writer Colin Thubron returns to fiction with his first novel in more than a decade, a searing, poetic masterwork of memory. A house is burning, threatening the existence of its six tenants...including a failed priest; a naturalist; a neurosurgeon; an invalid dreaming of his anxious boyhood; and their landlord, whose relationship to the tenants is both intimate and shadowy. At times, he shares their preoccupations and memories. He will also share their fate. In Night of Fire, the passions and obsessions in a dying house loom and shift, from those of the hallucinating drug addict in the basement to the landlord training his rooftop telescope on the night skies. As the novel progresses, the tenants' diverse stories take us through an African refugee camp, Greek Orthodox monasteries, and the cremation grounds of India. Haunting the edges of their lives are memories. Will these remembrances be consumed forever by the flames? Or can they survive in some form? Night of Fire is Colin Thubron's fictive masterpiece: a novel of exquisite beauty, philosophical depth, and lingering mystery that is a brilliant meditation on life itself"...